Implementation Sustainable Development Goals (SDGs) Through the Development of Badan Usaha Milik Nagari (BUMNag): A Case Study Nagari Mungka - Yuswarni; Fadhila, Eka; Firdaus, Achmad; Arizal (JOELS: Journal of Election and Leadership, 2024)
This research discusses the Sustainable Development Goals (SDGs) through the development of Nagari-Owned Enterprises (BUMNag) in Mungka District, Lima Puluh Kota Regency, as an integrated effort for economic, social, environmental, legal, and governance development at the nagari level (local wisdom for villages in West Sumatra). In this context, BUMNag acts as a new means and approach in utilizing the potential of Nagari Mungka to improve the welfare of its people. This is done by considering the opportunities and needs of the Nagari to 'accommodate', support, and consolidate economic businesses within the Nagari area, so that it becomes a new source of income for the Nagari government in improving the local economy. This research uses a qualitative method with a case study approach by considering literature or reference studies. The results showed that the establishment of BUMNag has not fully implemented the eighteen goals of the SDGs program in Nagari Mungka because it is not strengthened by locally based policies, namely village regulations. It can be concluded that the existence of BUMNag is currently not maximally utilized, and there is still a lack of a comprehensive work program.